Biological effects of the antihypertensive losartan under different ocean acidification scenarios. (1st January 2022) - Pusceddu, F.H.; Guimarães, M.M.; Lopes, L.O.; Souza, L.S.; Cortez, F.S.; Pereira, C.D.S.; Choueri, R.B.; Cesar, A.
Abstract: Since the last decade, several studies have reported the presence and effects of pharmaceutical residues in the marine environment, especially those of the antihypertensive class, such as losartan. However, there is little knowledge about the physiological effects of losartan in marine invertebrates regarding its behavior under possible coastal ocean acidification scenarios. The objective of this study was to evaluate biological effects on marine organisms at different levels of the biological organization caused by the compound losartan in water and sediment under coastal ocean acidification scenarios. Water and sediment samples were collected at five sites around the Santos Submarine Sewage outfall (SSO) and two sites around the Guarujá Submarine Sewage Outfall (GSO). Losartan was found in concentrations ranging from <LOD to 7.63 ng/L in water and from <LOQ to 3.10 ng/g in sediments. Statistical analysis showed interactive effects pH and losartan on the toxicity results. The water toxicity test with Echinometra lucunter embryos/larvae showed LOECs 50–100 mg/L, with values decreasing as the pH decreased. In the sediment assays, LOEC value for sea urchin embryo-larval development was 1.0 μg/g for all tested pHs. Regarding the lysosomal membrane stability assays with adult bivalves, a LOEC of 3000 ng/L was found for Perna perna in water exposure (both at pH 8.0 and 7.6). Effects for Mytella guyanensis were observed at environmentally relevant concentrations in sediment (LOEC = 3 ng/g at pH 8.0 and 7.6). This study demonstrated that coastal ocean acidification by itself causes effects on marine invertebrates, but can also increase the negative effects of losartan in waterborne exposure. There is a need to deepen the studies on the ecotoxicity of pharmaceutical residues and acidification of the marine environment. Graphical abstract: Image 1 Highlights: Losartan was quantified in samples of marine water (up to 7.63 ng/L) and sediment (up to 3.10 ng/g). Sediment spiked with an environmental concentration of losartan affected lysosomal stability. Losartan effects were pH dependent and pH effects were dependent on the concentration of losartan. Ocean acidification exacerbates the negative effects of losartan in waterborne exposure. Abstract : Ocean coastal acidification can exacerbate negative effects of losartan to marine organisms.